The development of orthographic and phonological representations in relation to linguistic transparency in Greek and English (L2) - Kyparissiadis, Antonios (2012)
The development of orthographic as well as phonological representations as a result of the functions of each language’s level of transparency is the main focus of the present work. Initially, a review of the relevant literature is presented with the most prominent theories behind the development of representations being introduced and critiqued. Furthermore, two experiments were conducted to investigate the relative contributions of orthography and phonology as well as of different size units in word recognition. Ten Greek subjects (n=10) with mean age of approximately 15 years and mean reading age in English of approximately 11 years participated and were tested in reading words and non-words in their native language and in English (L2). The nonsense words utilized either shared orthography and phonology, phonology only, or neither of the two with real words at the level of the rime. Analysis showed that the participants benefitted both from orthographic and phonological facilitation in terms of speed in both their native (transparent) and foreign language (non-transparent). They also showed an accuracy deficit when the cues were not present in the English stimuli but not in the Greek ones. These results are interpreted with respect to the differences that the level of transparency and the maturity of the reading skills can introduce in the development of the mental representations employed in word recognition.